EFEKTIVITAS PENGGUNAAN SENJATA API BAGI PERSONIL POLRI GUNA PENINGKATAN KINERJA DALAMPENANGGULANGAN TINDAK PIDANA DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PADANG - Marzuki, Alfias; Wibowo, Adhi (Universitas Ekasakti, 2019)
The use of firearms for police personnel has been regulated in Article 8 paragraph (1) Perkapolri Number 1 Year 2009 and Article 45 Perkapolri Number 8 Year 2009. Firearms for members of the Police who carry out the function of law enforcement is to make a forced effort through the action of paralyzing, stopping, inhibits the actions of a person or group of people. However, in practice there is still a misuse of the use of firearms carried out in the execution of tasks and outside the execution of duties. The results showed that the use of firearms to improve performance in the prevention of crime in Polresta Padang ranks has been effective because with the many personnel but who have few firearms and only two members who do the misuse of firearms of service not for the benefit of the service and the tendency of decreasing the number of criminal acts.